3-micron wave band mid-infrared polarization-independent graphene modulator - Lu, Rongguo; Shen, Liming; Wang, Yujiao; Cai, Songwei; Lin, Rui; Chen, Jinzhan; Yang, Zhonghua; Lyu, Jiangbo; Wang, Xiaoju; Liu, Yong (European physical journal plus, 2021)
A novel polarization-independent electro-absorption graphene modulator is proposed. Two layers of graphene structure are transferred on the inclined arsenic selenide and then covered with arsenic selenide to form a partially inclined graphene-arsenic selenide waveguide structure. According to the simulation results, TE and TM effective mode in the waveguide have almost the same change under different Graphene chemical potentials near the 3 μm wavelength. For the 100-μm-long waveguide structure, the extinction ratio (ER) of about 20 dB can be achieved through the selection of low absorption ("ON") and high absorption ("OFF") state points, and the gap between the two modes’ ER is less than 1.2 dB. The dependency of these two polarization states in "ON" state is lower than 0.112 dB, which indicates that the device can be used as polarization independent modulation. And combined with simulation calculations, the theoretical 3 dB modulation bandwidth ( f 3dB ) of the proposed modulator reaches 43.5 GHz.